Characterization of scientific production about friction injuries: integrative review (Research, Society and Development, 2021)
Objective: to identify scientific productions on Skin Tears injuries in the literature. Methodology: integrative review, searched between April and June 2020, in LILACS, PubMed, SCOPUS, SciELO, Web of Science and Cochrane databases to answer the guiding question: “What are the characteristics of scientific production on Skin-type injuries Tears?”. Original research articles that met the research objective were included. Gray literature studies (case reports, reflection, recommendations), review articles and studies that focused on other themes were excluded. Results: searches in the surveyed databases captured 371 references. After the exclusions, 13 studies were selected to be read in full, of which, 07 articles were selected to compose this review, empirically grouped, according to their similarities, into three categories: "Prevalence and risk factors for Skin Tears", "Importance of prevention and management of Skin Tears" and "Weaknesses of institutional protocols that standardize the care of Skin Tears". Conclusion: the theoretical approach to friction injuries is essential to provide effective care, aiming to minimize discomfort and complications in patients affected by them. However, there was a scarcity of studies that could support a discussion of quality, as it is essential to promote comprehensive care that guarantees a better quality of life.